Law, human rights and gender in practice: an analysis of lessons from implementation of self-care interventions for sexual and reproductive health. Issue 3 (1st January 2022) - Ferguson, Laura; Narasimhan, Manjulaa; Gutierrez, Jose; Jardell, William; Gruskin, Sofia
Abstract: Self-care interventions for health are becoming increasingly available, and among the preferred options, including during the COVID-19 pandemic. This research assessed the extent of attention to laws and policies, human rights and gender in the implementation of self-care interventions for sexual and reproductive health (SRH), to identify where additional efforts to ensure an enabling environment for their use and uptake will be useful. A literature review of relevant studies published between 2010 and 2020 was conducted using PubMed, Scopus and Web of Science. Relevant data were systematically abstracted from 61 articles. In March–April 2021, semi-structured interviews were conducted with 10 key informants, selected for their experience implementing self-care interventions for SRH, and thematically analysed. Laws and policies, rights and gender are not being systematically addressed in the implementation of self-care interventions for SRH. Within countries, there is varied attention to the enabling environment including the acceptability of interventions, privacy, informed consent and gender concerns as they impact both access and use of specific self-care interventions, while other legal considerations appear to have been under-prioritised. Operational guidance is needed to develop and implement supportive laws and policies, as well as to ensure the incorporation of rights and gender concerns in implementing self-care interventions for SRH.